1999
DOI: 10.1038/46072
|View full text |Cite
|
Sign up to set email alerts
|

Diverse behavioural defects caused by mutations in Caenorhabditis elegans unc-43 CaM Kinase II

Abstract: Calcium/calmodulin-dependent serine/threonine kinase type II (CaMKII) is one of the most abundant proteins in the mammalian brain, where it is thought to regulate synaptic plasticity and other processes. Activation of the multisubunit kinase by calcium is effectively cooperative and can persist long after transient calcium rises. Despite extensive biochemical characterization of CaMKII and identification of numerous in vitro kinase targets, little is known about its function in vivo. Here we report that unc-43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
139
2
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(150 citation statements)
references
References 30 publications
8
139
2
1
Order By: Relevance
“…It has been reported that unc-43 loss-and gain-of-function mutations cause, respectively, hypo-and hypercontraction of the bodywall muscles (Reiner et al 1995(Reiner et al , 1999. Indeed, the unc-43(n498)g f mutant displayed densely packed MYO-3T GFP muscle fibers (Figure 2c).…”
Section: Resultsmentioning
confidence: 93%
“…It has been reported that unc-43 loss-and gain-of-function mutations cause, respectively, hypo-and hypercontraction of the bodywall muscles (Reiner et al 1995(Reiner et al , 1999. Indeed, the unc-43(n498)g f mutant displayed densely packed MYO-3T GFP muscle fibers (Figure 2c).…”
Section: Resultsmentioning
confidence: 93%
“…CaM-KII is a calcium-activated protein and is known to influence gene expression (Kapiloff et al 1991;Ramirez et al 1997;Hughes et al 2001;Zhang et al 2004;Ronkainen et al 2011). In C. elegans, loss-of-function mutations in CaMKII/ unc-43 have profound deleterious effects on virtually every behavior of the worm (Reiner et al 1999). The unc-43 (sy574) allele we previously isolated causes males to display the Prc phenotype, but does not have any gross effect on other behaviors in males or hermaphrodites (LeBoeuf et al 2007(LeBoeuf et al , 2011.…”
Section: Resultsmentioning
confidence: 99%
“…unc-43 encodes CaMKII in C. elegans and regulates movement, defecation, and egg laying in addition to its role in male mating (Reiner et al 1999). We previously reported that loss-of-function mutations in CaM-KII cause C. elegans males to display the Prc phenotype.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we find that osr-1(rm1), pmk-1(RNAi) (N ϭ gate the potential relationship between OSR-1 and the most upstream component of the Nsy pathway, UNC-175); nsy-1(ky379), osr-1(RNAi) (N ϭ 1259); and sek-1 (km4), osr-1(RNAi) (N ϭ 376) animals remained resis-43. As shown in Figure 5A, UNC-43, the only identified CaMKII in C. elegans (Reiner et al 1999), was also retant to the acute effects of osmotic stress by maintaining normal swimming behavior (100% motile animals after quired for viability under chronic osmotic stress.…”
Section: Stressmentioning
confidence: 97%